Interaction effects on support for climate‐change mitigation. (29th October 2021) - Brown, Adrienne R.; Hamilton, Lawrence C.
Abstract: Background: Research on the social bases of environmental concern has established robust findings across various sociodemographic characteristics. This includes interaction effects between education and political identity, as well as particularly low concern among supporters of President Trump. Objectives: Using 2016 survey data, we extend such research to examine U.S. public support for four climate‐change mitigation strategies: investment in renewable energy, lifestyle changes, a revenue‐neutral carbon tax, and cap‐and‐trade. Methods: We perform ordered logit regression of belief in anthropogenic climate change and support for these strategies on several key independent variables. Results: Support follows some of the patterns expected for environmental concern generally but with new details. Trump support is a dominant predictor, and education × party interactions show significant variations in levels of support. Conclusion: This provides important insights for public policy decision making related to climate change by considering which characteristics are most predictive of support for specific strategies.